Innovative presentations for dummies - Anthony, Ray; Boyd, Barbara (Hoboken, New Jersey John Wiley and Sons, 2014)
"Be the leader audiences will follow with innovative presentations." Innovative Presentations For Dummies is a practical guide to engaging your audience with superior, creative, and ultra-compelling presentations. Using clear language and a concise style, this book goes way beyond PowerPoint to enable you to reimagine, reinvent, and remake your presentations. Learn how to stimulate, capture, and hold your audience in the palm of your hand with sound, sight, and touch, and get up to speed on the latest presentation design methods that make you a speaker who gets audiences.
Be the speaker they follow with breakthrough innovative presentations! This practical guide uses clear language and a concise style to enable you to reimagine, reinvent, and remake your presentations. From preparing for distracting responses and behavior to choosing the best hardware and apps for your needs, you'll gain the skills to present with confidence and power.
Introduction -- Getting started with innovative presentations -- The secrets of presentation success -- Giving a great presentation -- Mixing creativity and technology -- Tailoring the message -- The part of tens.
Includes index.
Keywords: Business presentations